An overview of neurobehavioral and developmental toxicity induced by xenoestrogens - Ranjit Shaw; Anmol S. Kamath; Radha Chaube (Discover Toxicology)
Abstract Endocrine-disrupting chemicals (EDCs), particularly xenoestrogens, are environmental pollutants that mimic or interfere with estrogen signalling pathways, impairing the endocrine system’s ability to function normally. These chemicals, found in industrial products such as plastics and personal care items, pose significant neurobehavioral and developmental risks, especially to vulnerable populations such as fetuses, infants, and children. Xenoestrogens exposure, even at low doses, has been associated with cognitive impairments, emotional dysregulation, and altered social behaviors, with sex-specific vulnerabilities further complicating the understanding of their effects. This review summarises current research on the mechanisms of xenoestrogens-induced neurotoxicity, including estrogen receptor activation, hormone metabolism disruption, and epigenetic modifications, which collectively contribute to adverse neurological outcomes. Furthermore, it explores the developmental impacts of exposure during critical brain maturation periods and highlights specific chemicals, such as bisphenol A (BPA), phthalates, and polychlorinated biphenyls (PCBs), as key contributors to neurodevelopmental disruption. Addressing the challenge posed by xenoestrogens will require integrated research, policy reform, and public health strategies aimed at reducing exposure, especially for susceptible populations.